Characterization of three new HLA Class I Alleles in Spanish Caucasians, HLA‐A*02:620, HLA‐B*27:150 and HLA‐B*07:05:01:02. (6th April 2017) - Balas, A.; Planelles, D.; Montesinos, P.; Solano, C.; Vicario, J. L.
Summary: Three new HLA class I alleles, HLA‐A*02:620, HLA‐B*27:150 and HLA‐B*07:05:01:02, were described in the Spanish Caucasoid population.